Project-Based Learning in Creating Edible Straws from Red Dragon Fruit Peel to Develop Science Process Skills - Nida Khalda; Risa Rahmawati Sunarya; Riri Aisyah; Iis Dahriah (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This study aimed to analyze the implementation of project-based worksheets utilizing red dragon fruit peel waste (Hylocereus polyrhizus) to develop students’ science process skills (SPS). The research employed a pre-experimental method with a one-shot case study design, conducted at a vocational high school in Cimahi City, involving 31 senior high school students from Class XI Industrial Chemistry-C. The research instruments consisted of student activity observation sheets, project-based worksheets, and SPS performance sheets. The results showed an average student activity score of 95%, a cognitive SPS score of 90%, and a psychomotor SPS score of 96%, all categorized as “excellent.” Hence, the project-based worksheet on producing edible straws from red dragon fruit peel waste was proven to be highly feasible and effective in developing students’ SPS.